Pengembangan Literasi Berbasis Inklusi Sosial Melalui Bedah Buku Sejarah Lokal: Sejarah Pembangunan Waduk Sermo Tahun 1994-1996 - Siska Nurazizah Lestari; Wahyu Pambudi; Nuryuana Dwi Wulandari; Nugraha Nugraha; Eurico Wahyu Al Lazuardi; Ghiza Aulia Ramadhan; Melinda Prahastiwi; Raden Roro Ninda Karrisma (Medan Resource Center, 2022)
This article aims to discuss the development of social inclusion-based literacy through reviewing local history books: the history of the construction of the Sermo Reservoir in 1994-1996. Literacy is an important thing to support the life of every individual, because every aspect of life can be explained through it. Therefore the community service team from the History Education Study Program FPIPS IPW together with the Kulon Progo Regency Library and Archives Service held an activity with the theme of Social Inclusion-Based Literacy Development through Local History Book Review: History of the Development of Sermo Reservoir 1994-1996. The stages carried out in this community service are observation, coordination, execution, and evaluation. Meanwhile the method used is lectures followed by discussion activities.